Coagulation factor V and thrombophilia: Background and mechanisms - Segers, Kenneth; Dahlbäck, Björn; Nicolaes, Gerry A. F. (Thrombosis and Haemostasis, 2007)
Human coagulation factor V (FV) is an essential coagulation protein with functions in both the pro- and anticoagulant pathways. Failure to express and control FV functions can either lead to bleeding, or to thromboembolic disease. Both events may develop into a life-threatening condition. Since the first description of APC resistance, and in particular the description of the so-called factor VLeiden mutation, in which a prominent activated protein C cleavage site in FV has been abolished through a mutation in the FV gene, FV has been in the center of attention of thrombosis research. In this review we describe how the functions of FV are expressed and regulated and provide an extensive description of the role that FV plays in the etiology of thromboembolic disease.
Keywords: Factor V; coagulation; thrombosis; thrombophilia; protein C pathway